The effect of an educational program based on the constructivist learning model in developing critical thinking skills through social studies for third grade learners.In the city of Jableh (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research aims to determine the impact of using the constructivist learning model in developing critical thinking skills through social studies. The research sample consisted of (70) male and female students divided into two groups: the experimental group included (35) male and female learners who learned according to the constructivist learning model, and The control group included (35) male and female learners who learned according to the usual method, and the critical thinking skills test was applied to both groups together. The results of the research indicated that there were statistically significant differences between the experimental and control groups in favor of the experimental group in relation to the critical thinking skills test due to the variable (constructive learning model).